Optimizing Learning Environments: Strategic Planning, Organizing, and Storage Techniques Needed for Building Construction Workshops in Technical Colleges - Gana, D.; Mohammed, U.; Kumazhege, S. Z. (Journal of Multidisciplinary Science: MIKAILALSYS, 2024)
The main purpose of the study was to optimize the learning environments through strategic planning, organizing, and storage techniques needed by teachers for building construction workshops in technical colleges. The study was guided by three specific objectives, three research questions as well as three null hypotheses conducted in Gombe State using descriptive survey research design. The population for the study was 63 individuals, consisting of 21 School Administrators, 28 Building Construction Teachers, and 14 Workshop Staff from all Government Science and Technical Colleges in Gombe State. There was no sampling as the entire population was used because it was manageable. A structured questionnaire tagged titled "Management of Building Construction Workshop for Effective Teaching and Learning Questionnaire (MTBCWETLQ)," divided into four sections (A-D) covering personal data (Section A) and addressing the research questions (Sections B-D). The instrument was validated by three experts from Department of Technology Education, Modibbo Adama University of Technology Yola. A trial test conducted on 10 building construction teachers, 10 workshop staff, and 6 administrators in Adamawa State, outside the study area, yielded a reliability index of 0.90 using the Cronbach alpha method. Data collected for the study was analyzed using Statistical Package for Social Sciences (SPSS) version 26.0. Mean statistics was used to answer the three research questions while ANOVA was used to test the hypotheses at 0.05 level of significance. Findings of the study revealed among others that Planning techniques for managing building construction workshops involve identifying machine locations for safety, arranging facilities based on student enrollment projections, setting up layouts with clear student roles, and establishing appropriate workshop durations. Organizing techniques include arranging tools and materials before and after use, ensuring an efficient flow of materials, selecting equipment based on learning activities, and organizing materials according to their uses for enhanced supervision and safety. It is recommended that Staff involved in managing building construction workshops should undergo training or workshops to improve their planning techniques. Staff should be encouraged to adopt more effective organizing techniques in building construction workshops.